Makna Simbolik dan Nilai Kearifan Lokal dalam Tradisi Meron di desa Sukolilo Kabupaten Pati - Dany Miftah M. Nur; Alfina Nor Aini; Musdalifah Musdalifah; Octaviana Azizah; Muhammad Ulil Albab (Journal on Education, 2024)
The Meron tradition in Sukolilo Village, Pati Regency, is a unique celebration which aims to celebrate the birthday of the Prophet Muhammad SAW every 12 Robiul Awal. Similar to the Sekatenan traditions of the Surakarta Palace and the Ngayogyakarta Palace, the Meron tradition contains symbolic meaning and local wisdom values that have an impact on aspects of people's lives. This research used a qualitative descriptive method involving participants from the Sukolilo Village community. The research results show that the Meron tradition has symbolic meaning which includes religious aspects, da'wah, community harmony and cultural preservation. Values such as religious, social, artistic and economic are reflected in the implementation of this tradition. Conservation efforts are carried out through active community participation in holding traditional ceremonies every year, with a focus on protecting, developing and utilizing local culture. Ethics in the Meron ceremony is the key to continuity between generations, ensuring that cultural heritage remains alive and well maintained. The Meron tradition is not just a celebration, but also a cultural heritage full of meaning and value. Efforts to preserve it are important to ensure the sustainability and meaningfulness of this tradition in the lives of the people of Sukolilo Village, Pati Regency.